Instrument rules in monetary policy under heterogeneity in currency trade - Mikael Bask (Bank of Finland, 2007)
We embed different instrument rules into a New Keynesian model for a small open economy that is augmented with technical trading in currency trade to examine the prerequisites for monetary policy. Specifically, this paper focuses on conditions for a determinate, least-squares learnable rational expectations equilibrium (REE). Under an interest rate rule with only contemporaneous macroeconomic data, the intensity of technical trading or trend-seeking in currency trade does not affect these conditions, except in the case of an extensive use of trend-seeking. On the other hand, if the central bank uses only forward-looking information in its interest rate rule, a determinate and learnable REE is a less likely outcome when trend-seeking in currency trade becomes more popular. The interest rate rule followed by the central bank in the model incorporates interest rate smoothing.
URN:NBN:fi:bof-20140807386
Keywords: C62; E52; F31; F41; 330; determinacy; DSGE model; interest rate rule; least-squares learning; technical trading